(untitled) (International Journal of Environmental Sciences, 2025)
Background: The bacteria was considered one of the main microorganism in the ecosystem particularly, performing numerous functions in the environment, which maintain ecosystem balance, including pollutant degradation and biodegradation of toxins. Aim of study: Soil and water bacterial screening from different locations in Basrah city, Iraq. Methods: Fifty sterile container were used for collection of 50 samples (25 Soil and 25 Water) from different sites of soil and water in Al-Basrah city. DNA was extracted from environmental bacteria using the total DNA extraction Kit following the manufacturer’s protocol for Presto™ Mini g DNA bacteria (Genaid). The Basic Local Alignment Search Tool software (BLAST) was used for identification of bacterial species and using the National Center for Biotechnology Information (NCBI). Results: we recorded 13 isolates of bacteria from soil and water in the south Iraqi as a new global species depending on the extraction of DNA followed by 16S rRNA gene PCR amplification and sequencing data analysis. These 13 new isolates were recorded in Basrah province including Staphylococcus gallinarum, Psychrobacter nivimaris, Terribacillus aidingensis, Bacillus cabrialesii, Photobacterium halotolerans, Bacillus paramycoides, Rheinheimera baltica, Staphylococcus saprophyticus, Micrococcus endophyticus, Rheinheimera aquimaris, Zobellella denitrificans, Pseudomonas zhaodongensis, Pseudomonas hydrolytica. Conclusion: Our recorded 13 types of bacteria from soil and water in the south Iraqi. These species were documented as new records in Iraq, while others were index in the National Center for Biotechnology Information (NCBI), the European Nucleotide Archive (ENA), and the DNA Data Bank of Japan (DDBJ) in sequence.